1971
DOI: 10.1149/1.2407852
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence of Alkaline Earth Thiosilicate Phosphors

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…For this phosphor it was argued that Eu substitution on the two different Ca sites in the host lattice gives two distinct emission bands, at about 560 and 650 nm, with the relative intensity of both bands depending on the Eu 2+ concentration. Although the emission band at longer wavelengths was related by Avella to trace amounts of CaS:Eu 2+ [15], we argued that it could be related to the pres- ence of two different lattice sites in Ca 2 SiS 4 [10]. From the fact that the emission spectrum of Ca 2 SiS 4 :Ce 3+ changes when varying the excitation wavelength and dopant concentration, it can be derived that also for Ce 3+ more than one emission centre is active.…”
Section: Photoluminescence Of Ca 2 Sis 4 :Ce 3+mentioning
confidence: 73%
See 1 more Smart Citation
“…For this phosphor it was argued that Eu substitution on the two different Ca sites in the host lattice gives two distinct emission bands, at about 560 and 650 nm, with the relative intensity of both bands depending on the Eu 2+ concentration. Although the emission band at longer wavelengths was related by Avella to trace amounts of CaS:Eu 2+ [15], we argued that it could be related to the pres- ence of two different lattice sites in Ca 2 SiS 4 [10]. From the fact that the emission spectrum of Ca 2 SiS 4 :Ce 3+ changes when varying the excitation wavelength and dopant concentration, it can be derived that also for Ce 3+ more than one emission centre is active.…”
Section: Photoluminescence Of Ca 2 Sis 4 :Ce 3+mentioning
confidence: 73%
“…As no detailed information is available in literature on the emission properties of Ca 2 SiS 4 :Ce 3+ , its luminescence was investigated as a function of the Ce 3+ concentration. Avella did not show emission spectra but reported the cathodoluminescence efficiency to be low [15]. Fig.…”
Section: Photoluminescence Of Ca 2 Sis 4 :Ce 3+mentioning
confidence: 92%
“…Beside structural characterization of Ca 2 SiS 4 (space group P nma , orthorhombic [15]) and Eu 2 SiS 4 (space group P2 1 /m, monoclinic [16]), the luminescent properties of Ca 2 SiS 4 :Eu have been explored only briefly. Avella reported that the cathodoluminescence is characterized by an emission peak at 563 nm [14]. A second emission band peaking at 660 nm was also observed, and tentatively assigned to the presence of CaS:Eu in the synthesized powder.…”
Section: Introductionmentioning
confidence: 75%
“…These values are in line with the measurements reported by Avella. Avella studied the cathodoluminescence of Sr2SiS4:Ce3+ and reported the intensity to be weak [26]. In photoluminescence, however, for sufficiently low concentrations (less than 1%) and excited with light of 400 nm, the phosphor shows a bright emission intensity.…”
Section: Resultsmentioning
confidence: 99%